Pengaruh Penerapan Model Problem Based Learning Menggunakan Media Flipbook pada Materi Ekosistem dan Interaksinya terhadap Kemampuan Berpikir Kritis Siswa Kelas X MAN 2 Samarinda - Nurhayati Nurhayati; Zenia Lutfi Kurniawati; Akhmad Akhmad; Suparno Putera Makkadafi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the effect of implementing a Problem-Based Learning (PBL) model assisted by flipbook media on the topic of ecosystems and their interactions on the critical thinking skills of tenth-grade students at MAN 2 Samarinda. This study used a quantitative approach with a quasi-experimental pretest-posttest control group design. The analysis results showed that the N-Gain value in the experimental class was 0.57 (medium category), higher than that in the control class. The independent sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant effect of implementing a PBL model assisted by flipbook media on students' critical thinking skills. These findings indicate that the use of a flipbook-based PBL model is effective in improving critical thinking skills in biology learning.